A mimic of soft tissue infection: intra-arterial injection drug use producing hand swelling and digital ischemia - Foster, Sean D. (World J Emerg Med, 2015)
BACKGROUND: Inadvertent intra-arterial injection of illicit substances is a known complication of injection drug use and can lead to severe complications, including infection, ischemia and compartment syndrome. Identifying complications of intra-arterial injection can be difficult, as clinical manifestations overlap with other more common conditions such as cellulitis and soft tissue infection, and a history of injection drug use is frequently not disclosed. METHODS: A 37-year-old male patient presented with 24 hours of right hand pain, erythema and swelling. Despite classic “track marks”, he denied a history of injection drug use, and vascular insults were not initially considered. After failing to respond to three days of aggressive treatment for suspected deep-space infection, an arteriogram demonstrated findings consistent with digital ischemia of embolic etiology. RESULTS: As a result of the delay in diagnosis, the lesion was not amenable to reperfusion and the patient required amputation of the distal digit. CONCLUSION: Practitioners should be alert to the possibility of intra-arterial injection and resulting complications when evaluating unusual extremity infections or unexplained ischemic symptoms, even in the absence of a definite history of injection drug use.